ANALISIS PELAKSANAAN PROGRAM KERJA PUSKESMAS BERDASARKAN PERMENKES NOMOR 75 TAHUN 2014 TENTANG PUSAT KESEHATAN MASYARAKAT DI KOTA BUKITTINGGI TAHUN 2017 - Khairul Abbas (Universitas Fort De Kock, 2020)
The Community Health Center is a health service facility that carries out public health efforts and individual first-level health efforts, by prioritizing promoting and preventive efforts, to achieve the highest level of public health in its working area. Yet, this time most of the programs in community health centre is just However, this time, most of existing community health centre programs should be promotive and preventive, but in reality the activities carried out by community health center on a daily basis remain curative and rehabilitative. Promotive and preventive programs that have been well designed in the community health centre often do not run well based on the previous aim. This research was conducted in April 2018, by using a qualitative method with a phenomenological approach, data collection is done by using interview guidelines, observation, and document study through deep interviews. Based on the research conducted, it was found that the Ministry of Health Rules No. 75 of 2014 has not yet been applied to the Community Health Center to the maximum in the Bukittinggi City Health Center. This is caused by some factors, several obstacles includes facilities and infrastructure, human resources and funding. It is expected that the Government's attention to the existing problems in order to create quality services to achieve the highest level of health. Keywords : Community Health Centre, Promotive, Preventive References : 112 (2002 - 2017)